Сalculation of optimal parameters for a vibratory finishing machine for decorative elements with an active working tool - Buhrov, Dmytro; Buhrova, Tetiana (Academic journal Industrial Machine Building Civil Engineering, 2023)
The calculation of optimal parameters for a new design vibration installation with an active working body is proposed using numerical methods. By modeling the system as a mass-spring-damper system and applying harmonic Fourier analysis of the vibrations, a mathematical model of the dynamic interaction between the working body and the part was obtained, taking into account additional friction forces, the angle of inclination, and elastic and damping forces. The key determined parameters—phase shift between the vibrations of the working body, the part, and the abrasive. An example of calculating optimal parameters using the gradient descent method is provided. Based on the calculation results, comparative time graphs of the phase shift of vibrations of the part and the working body, as well as amplitude, were constructed.